Age-Graded Heterogeneity in the Relationship Between Hours of Work and Crime - Jaynes, Chae M. (Criminal justice and behavior, 2023)
Criminal justice researchers have focused on theoretical thresholds of work and their association with offending—such as “full-time” work among adults or “intense” work among adolescents. Despite the field’s reliance on these thresholds, there has been little empirical inquiry surrounding them. Using individual-level fixed effects and a sample of high-risk individuals, we evaluate age-graded heterogeneity in the relationship between hours of work and crime. Findings suggest that the association between hours of work and offending is negative and mostly linear among adults. However, the relationship is far more complex among adolescents, as it varies greatly by crime type and the specific number of hours worked. We discuss the practical implications of these findings with the suggestion that researchers and policy makers reconsider oversimplified work thresholds, as working more hours is not uniformly criminogenic among high-risk adolescents, whereas more hours worked is generally beneficial for young adults.